'Strong leaders', authoritarian populism and Indian developmentalism: The Modi moment in historical context. Issue 124 (August 2021) - Sinha, Subir
Abstract: India's Prime Minister Narendra Modi is part of a worldwide wave of strong 'populist' leaders who have emerged in the context of the crisis of neoliberalism, and among whose appeal is their claims to put their economies back on a growth trajectory by the authoritarian implementation of core neoliberal reforms. Noting its relative lack in relevant literatures, I build an account of 'strong leadership', based on Modi's record in government, as it mediates between 'authoritarian populism' and 'neoliberal restoration'. Such leadership, I show, is based on a serial creation of a 'people/enemy' divide in society, mobilising this division to win large electoral mandates, and using and using such mandates in turn to support authoritarian projects of majoritarianism and of neoliberal economic reforms. Modi has drawn on leadership practices contextual to postcolonial India, such as earlier iterations under Nehru and Indira Gandhi. However, his project has moved beyond these earlier iterations of 'strong leader' politics into an authoritarian and, in some crucial ways, fascist directions. Coming to power to solve the 'crisis of neoliberalism', it has made most advance in instituting a majoritarian Hindu nation, first constructing it as a pre-figurative community, and now giving it shape as constitutional fact. These new modes of 'embodying the nation' and exercising spatial control have been made possible through the domination of media and social media that create serial 'radical exclusions' of nominated 'enemies of the people'. However, his project of joining an authoritarian restoration of some key neoliberal policy themes with the pursuit of a Hindu nation is limited by how much contention can be contained within the 'people-enemy' frame, and by changes in other enabling conditions of international support and social media domination.